2010
DOI: 10.1185/03007995.2010.537589
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of tapentadol ER in patients with painful diabetic peripheral neuropathy: results of a randomized-withdrawal, placebo-controlled trial

Abstract: Compared with placebo, tapentadol ER 100-250 mg bid provided a statistically significant difference in the maintenance of a clinically important improvement in pain 1 , 2 and was well-tolerated by patients with painful DPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(127 citation statements)
references
References 46 publications
3
118
1
5
Order By: Relevance
“…First, pioglitazone and other PPARγ agonists reduce neuropathic pain-like behavior in normoglycemic animals after various routes of administration including: repeated oral 55, 63 or intraperitoneal 31, 55, 63, 96 ; local injection to the injured sciatic nerve 96 or incised paw 31 ; or a single spinal 11, 30, 62, 71 or brain 62 injection. Second, numerous drugs can reduce PDN without reducing hyperglycemia in patients with PDN, including tapentadol 88 or the FDA-approved PDN medications duloxetine and pregabalin 59, 90 . Furthermore, the antioxidant taurine 49 , aldose reductase inhibitors 9, 66, 75 , insulin growth factor 112, 113 , or poly-ADP-ribose inhibitors 21, 67, 68 reduce hyperalgesia in animal models of PDN without inhibiting hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…First, pioglitazone and other PPARγ agonists reduce neuropathic pain-like behavior in normoglycemic animals after various routes of administration including: repeated oral 55, 63 or intraperitoneal 31, 55, 63, 96 ; local injection to the injured sciatic nerve 96 or incised paw 31 ; or a single spinal 11, 30, 62, 71 or brain 62 injection. Second, numerous drugs can reduce PDN without reducing hyperglycemia in patients with PDN, including tapentadol 88 or the FDA-approved PDN medications duloxetine and pregabalin 59, 90 . Furthermore, the antioxidant taurine 49 , aldose reductase inhibitors 9, 66, 75 , insulin growth factor 112, 113 , or poly-ADP-ribose inhibitors 21, 67, 68 reduce hyperalgesia in animal models of PDN without inhibiting hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Tapentadol has been shown to be effective in the management of different types of chronic pain, including osteoarthritis knee pain, low back pain and DNP, with a tolerable safety profile [168,169] . Specifically concerning DNP, a randomizedwithdrawal, placebocontrolled trial reported reduction of at least 30% in pain intensity in about 50% of the patients that received tapentadol [170] . Similar data were obtained in a recent clinical trial in diabetic neuropathic patients with moderate to severe pain, which experienced nausea (21.1%) and vomiting (12.7%) as side effects [171] .…”
Section: Opioidsmentioning
confidence: 99%
“…Tapentadol has been shown to be effective in the reduction of pain intensity 227,228 , Vinik et al 227 reported improvement in pain in PC-RCTs. The pain reduction occurs within 2–3 weeks 227 .…”
Section: Findings From Studies Grouped By Chronic Pain Syndromementioning
confidence: 99%
“…The pain reduction occurs within 2–3 weeks 227 . The minimal effective dose ranged from 100 mg/daily 227,228 . Tramadol has been shown to be effective in the reduction of pain intensity and improvement in social and physical functioning in a single PC-RCT 229 .…”
Section: Findings From Studies Grouped By Chronic Pain Syndromementioning
confidence: 99%